Polyfunctional CD4+ T Cells As Targets for Tuberculosis Vaccination - Lewinsohn, Deborah A.; Lewinsohn, David M.; Scriba, Thomas J. (Frontiers in Immunology, 2017)
Tuberculosis (TB), caused by M. tuberculosis (Mtb), remains a leading cause of morbidity and mortality worldwide, despite widespread use of the only licensed vaccine, Bacille Calmette Guerin (BCG). Eradication of tuberculosis will require a more effective vaccine, yet evaluation of new vaccine candidates is hampered by lack of defined correlates of protection. Animal and human studies of intracellular pathogens have extensively evaluated polyfunctional CD4+ T cells producing multiple proinflammatory cytokines (IFN-, TNF-, IL-2) as a possible correlate of protection from infection and disease. Herein, we review the published literature that evaluates whether or not BCG and/or novel TB vaccine candidates induce polyfunctional CD4+ T cells and if these T cell responses confer correlate with vaccine-mediated protection. Ample evidence suggests that BCG and several novel vaccine candidates evaluated in animal models and humans induce polyfunctional CD4+ T cells. However, while a number of studies utilizing the mouse TB model support that polyfunctional CD4+ T cells are associated with vaccine-induced protection, other studies in mouse and human infants demonstrate no correlation between these T cell responses and protection. We conclude that induction of polyfunctional CD4+ T cells is certainly not sufficient and may not even be necessary to mediate protection and suggest that other functional attributes, such as additional effector functions, T cell differentiation state, tissue homing potential or long-term survival capacity of the T cell may be equally or even more important to promote protection. Thus, a correlate of protection for TB vaccine development remains elusive. Future studies should address polyfunctional CD4+ T cells within the context of more comprehensive immunological signatures of protection that include other functions and phenotypes of T cells as well as the full spectrum of immune cells and mediators that participate in the immune response against Mtb.